Mullasadra and semantics - Hassan Hamtaii; ali akbar ahmadi (حکمت اسرا)
A derivative (mushtaq) in Sadra’s philosophical jargon, he claims, is what mystics call as “name” (Ism). Elsewhere proposing a subtle distinction between names, descriptions and essences he mentions the word “name” on a par with derivatives. In Mafatih-alghayb he puts this view forward that opposite to real things, mental universal intelligibles are capable of being referred by names. Moreover he claims that there is a hierarchy (species, genus…) of names in divine world on a par with things in real world. Later he rejects the very point of view that only universal essences (quiddities) are capable of being named and surprisingly add particulars as well as secondary intelligibles to the inventory of those who are referred by names. He seems to enjoy an incredible double status in talking about meanings; a narrow point of view and a wide one; the latter being more evident when addressing reference-less names and name-less references. To be sure, the most novel aspect of Sadra’s theory is on naming the God (Allah). In Al-Asfar, he argues that the name of the God is a name for everything, and the reference of his name, is what referred to by every name. Having this singular property be satisfied, it is hard, if possible, to match ordinary theories of meaning to that of Sadra. That’s why I think those philosophers, Sajjad Rizvi for example, who use modern jargon in their interpretations of Sadrian theory of meaning, do mistakes.